Enhancing Students’ Scientific Literacy through Socio-Scientific Issues-Based Project-Based Learning in Physics Education - Doni Nurdiansyah; Dadan Ramdany; Duden Saepuzaman (Jurnal Pendidikan Fisika, 2026)
Students’ scientific literacy in physics remains a major concern because classroom instruction often emphasizes conceptual understanding and mathematical problem-solving without sufficiently connecting physics concepts to real-life socio-scientific contexts. This study aimed to examine the effectiveness of Socio-Scientific Issues-based Project-Based Learning (SSI-PjBL) in improving eleventh-grade students’ scientific literacy in physics education. A quantitative quasi-experimental method with a non-equivalent control group design was employed. The study involved 67 students from a private senior high school in Bandung, Indonesia, divided into an experimental group and a control group. The experimental group received SSI-PjBL instruction, while the control group received conventional instruction. Data were collected using a scientific literacy test developed based on three core competencies: explaining scientific phenomena, evaluating and designing scientific inquiry, and interpreting data and scientific evidence. The data were analyzed using descriptive statistics, normalized gain (N-Gain), an independent samples t-test, and Cohen’s d effect size. The results showed that the experimental group achieved a greater improvement in scientific literacy than the control group. The experimental group obtained an N-Gain score of 0.61, categorized as moderate, whereas the control group obtained an N-Gain score of 0.33, categorized as low. The independent-samples t-test indicated a significant difference between the two groups (p < 0.05), with a large effect size (Cohen’s d = 0.92). Improvement was observed across all scientific literacy indicators, with the highest gain in explaining scientific phenomena. The novelty of this study lies in integrating socio-scientific issues with project-based learning as a contextual instructional strategy for physics education. The findings conclude that SSI-PjBL effectively enhances students’ scientific literacy by supporting the application of physics concepts to authentic problems. This study contributes to physics education by providing empirical evidence for a student-centered, contextual, and project-based approach aligned with 21st-century science learning goals.